Characteristics of Nanosecond Pulsed Discharges in Atmospheric Helium Microplasmas - Jugroot, Manish (Plasma science & technology, 2016)
Microplasmas are very interesting due to their unique properties and achievable regimes maintained at atmospheric pressures. Due to the small scales, numerical modeling could contribute to the understanding of underlying phenomena as it provides access to local parameters--and complements experimental global characteristics. A self-consistent formalism, applied to nanosecond pulsed atmospheric non-equilibrium helium plasmas, reveals that several successive discharges can persist as a result of a combined volume and dielectric surface effects. The valuable insights provided by the spatiotemporal simulation results show the critical importance of coupled gas and plasma dynamics--namely gas heating and electric field reversals.